Of Bricks and Glass: Learning to Accommodate the Everyday Rhythms of Home. (2nd September 2017) - Carr, Chantel; Gibson, Chris; Farbotko, Carol
Abstract: Much of the growing focus of research on home cultures and materiality emphasizes eventful or disruptive temporalities: extensions, renovations, retrofits. Here, we trace how homes and lives are reshaped materially and conceptually, in response to other less disruptive temporalities of accommodation. Interviews with suburban Australian households reveal how people gradually come to know the built fabric of their home over time. Lay expertise is acquired through small material adjustments across multiple timescales: triggered by overlapping rhythms of body and building amidst broader lifecourse rhythms. To explore the role material engagements play in mediating these rhythms we focus on two ubiquitous suburban materials—glass and brick. We seek to demonstrate how bodies learn to work with the qualities of these materials and adjust their rhythms to engender comfort through dwelling in place over time. These comparatively mundane processes of spatial, behavioral and material adjustment take on further significance when connected with questions of entrenched routines and practices, material stewardship, vulnerability, and the ability of households to adapt to a changing climate.